Pemenuhan Hak Warga Binaan dalam Undang-Undang No 22 Tahun 2022 Tentang Pemasyarakatan di Lapas Kelas II B Tasikmalaya Perspektif Siyasah Dusturiyah - Muhammad Risam Purnama (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Legally, inmates in prison experience the deprivation of their right to independence. However, this does not mean that inmates have no rights at all. Through Law No. 22 of 2022, the rights of inmates are determined by a number of 12 rights which must be fulfilled by prison officers. This research aims to discuss how prisoners' rights are fulfillment in Tasikmalaya Class II B Prison and the obstacles encountered in the field. The research was conducted using juridical-empirical methods and collected primary data through interviews and observations as well as literature review (qualitative). The main factor that becomes an obstacle to fulfilling the rights of inmates is the condition of the residents' excess capacity. Apart from that, factors that hinder the fulfillment of the rights of inmates are also determined by the condition of the structure, budget, political policies and infrastructure.